Treatment of Tinea Corporis by 0.50% Topical Ointment Prepared from Calvatia Craniformis Mushroom - Rasheed, Mahmood S; Al-shimary, Wathik M; Khamees , Azher S; Jameel , Ghassan H (Diyala Journal of Medicine, 2019)
Background: Tinea Corporis or Ringworm is a fungal disease caused by Trichophyton rubrum,T.mentagrophytes , Microsporum canis andT.tonsurans.It is transmitted by direct contact with infected animals and humans or by indirect contact through fomites. The Aim of Study: This study aims to evaluate the efficacy of 0.50% ointment prepared from Calvatia craniformis mushroom in treatment of Tinea Corporis in human. The Patients and Methods : The study is done in dermatology clinic in Baquba city. Three different concentration of Calvatia craniformis mushroom ointment are prepared by mixing three different weights of mushroom powder (0.3 ,0.4 and 0.5gm) with vaseline and completed up to 100 gm for each concentration to obtain (0.3%,0.4% and 0.5%) of the mushroom ointment respectively and then applied topically to lesion twice daily. Sixty patients were involved in our study and divided into two groups, the treatment group includes thirty patients which is divided into three subgroups, each subgroup include ten patients they were treated by one of the three concentrations ( Ten patients 0.3% , Ten patients 0.4%, Ten patients 0.5% concentrations). The control group included thirty patients was treated by 1% clotrimazol cream. Results and Conclusion: 0.5% mushroom ointment significantly reduce clearance time (P<0.05)in comparison with the control group , while other concentration produce non significant changes in clearance time , therefore this substance is effective in the treatment of tinea corporis with less time, more patient compliance compared with the control group.